Diagnostics to support mycetoma management—Development of two target product profiles. Issue 12 (14th November 2022) - Fongwen, Noah; Asiedu, Kingsley B.; Bakhiet, Sahar; Bonifaz, Alexandro; Cruz, Israel; Argaw, Daniel; Estrada‐Chavez, Guadalupe; Fahal, Ahmed H.; Litvintseva, Ana; Marks, Michael; Salinas‐Carmona, Mario C.; Sow, Doudou; et al.
Abstract: Objective: Mycetoma is a neglected tropical disease caused by more than 70 different microorganisms and identified by the WHO as one of the high‐priority diseases for developing diagnostic tests. To ensure the production of diagnostic assays for use by clinical staff in endemic regions, target product profiles (TPPs) were designed. Methods: We describe the development of two TPPs: one for a diagnostic test able to identify the causative agent of mycetoma and another that would determine when treatment could be stopped. The TPPs were developed by considering product use, design, performance, product configuration and costs. Results: Version 1.0 TPPs for two uses were posted by WHO for a 1‐month online public consultation on 25 October 2021, and the final TPP was posted online on 5 May 2022. Conclusion: A major difficulty encountered in developing both TPPs was the large number of agents able to cause mycetoma and the lack of specific biomarkers for most of them.